Parametric Design Optimization of Reverse Thrust Blades and Analysis of Fluid-Solid Coupling - Huicheng, Yang; Qingzhen, Yang; Canliang, Wang; Jin, Bai (Frontiers in Energy Research, 2022)
The parametric design method of equal and unequal thickness reverse thrust blades is studied based on the cubic Bessel curve controlled by four control points. In order to improve the aerodynamic performance of the thrust reverser and reduce the structure weight, the geometry shape of the blade in the three-dimensional thrust reverser cascade assembly was optimized by using a genetic algorithm based on BP artificial neural network, and the fluid-structure coupling and modal analysis of the optimized thrust reverser cascade were carried out. The results show that: compared with the benchmark model, the thrust reverses of the optimized equal thickness and non-equal thickness blades are increased by 15.64 and 12.71%, respectively, and the flow rate increases by 11.32 and 13.52%, respectively; based on the optimized blade profile, increasing the number of stiffeners is more efficient than increasing the thickness of cascade assembly in the area of reducing the maximum stress and strain; Increasing the number of stiffeners and the thickness of cascade assembly can improve the first-order natural vibration frequency of the cascade assembly.